“WORKING LIVES”: THE USE OF AUTO/BIOGRAPHY IN THE DEVELOPMENT OF A SOCIOLOGICAL IMAGINATION - Stephenson, Carol; Stirling, John; Wray, David (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2016)
This article critically evaluates the attempt of the authors to develop a sociological imagination within first-year undergraduate students studying the discipline of sociology at a British university. Through a sociological analysis of biography and autobiography (of both teachers and students), we attempted to create a quality of mind that would provide our students with the necessary sociological skills to critically interrogate different sociological forms, and allow them not simply to understand the subject as an academic discipline but also as a personally transformative experience. It was evident from the feedback from a number of student cohorts that the connection between sociology and the lived experience and personal consciousness had a profound and empowering impact on those who came to develop that quality of mind. “WORKING LIVES” : UTILISER L’AUTO/BIOGRAPHIE POUR DÉVELOPPER UNE IMAGINATION SOCIOLOGIQUE Dans cet article, nous évaluons de manière critique la démarche de développement d’une imagination sociologique que nous avons entreprise auprès d’étudiants inscrits en première année du baccalauréat en sociologie d’une université britannique. Effectuant une analyse sociologique de biographies et autobiographies de professeurs et d’étudiants, nous avons tenté de créer une qualité d’esprit pouvant donner aux étudiants les compétences sociologiques nécessaires à l’examen critique de différentes formes sociologiques. Ainsi, nous leur permettons non seulement de comprendre la sociologie en tant que discipline académique mais également comme expérience personnelle transformatrice. Selon la rétroaction obtenue auprès d’un grand nombre de groupes d’étudiants, il apparaît évident que la relation entre la sociologie, l’expérience vécue et la conscience personnelle a eu une influence profonde et stimulante sur ceux ayant développé cette qualité d’esprit.